SENI LUKIS OPLOSAN SENI YANG DEKAT DENGAN MASYARAKAT - DIDUNG PUTRA PAMUNGKAS (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2016)
Art is so close to the people, an artist creates a work of art is also so close from their people. Then a work of art created and appreciated by people. With art, an artist deliver an idea or ideas to be delivered to the general public. Art and the people a kind of relationship that both need each other and complement each other, each formed and shaped. Therefore, painting movement oplosan have purpose to get closer to the general public. It’s why the movement of painting oplosan always done in public places.oplosan painting is painting that in its creation mixing technique, materials, and may also be thought or idea, who performed together in one place is determined.